Eksploitasi Perempuan Oleh Media Cetak Ditinjau Dari Aspek Hak Asasi Manusia:Kajian Di Sejumlah Tabloid Di Wilayah DKI Jakarta - Sekar, Dwi Amalia Chandra (UI Scholars Hub, 2006)
In the end of 90’s, the circulation of mass media tend to more and more presenting women as an object of fascination to increase the amount sales. The appearance of women models in some national tabloids seem to be abundant and interrupt the society’s ethics and moral value. In the other hand, the tabloid is easy to get and sold cheaply. There are two opinions that concerning of the understanding of exploitation, First, There is no exploitation to the women in mass media, because women models do not feel exploited. It is undeniable that almost 80% women models in tabloid are prostitutes. Second, there are exploitations to women in mass media, because there are manipulations and exploitations by irresponsible publisher to increase their benefits, such as undesirable uploaded photos, publicizing photos without model permission, inappropriate salary or even they do not get any compensation at all. Exploitation that happened increasingly because there is no available law and regulation to protect the women from media exploitation. The consumer assumption that appearance instructed as pornography. For the moment, the